Forty years of environmental risk perceptions - Malnar, Brina (Teorija in praksa, 2012)
This paper examines a forty-year dynamic of concern for the environment among Slovenian respondents. It first makes an inventory of the variables that are presumed to influence perceptions of environmental risk, then proceeds to analyse twelve Slovenia Public Opinion datasets to observe the trends. The longitudinal evidence reveals considerable shifts in the perception of environmental concern, particularly in response to dramatic outside events (such as Chernobyl). The trends reveal a cyclic pattern, with 2011 levels of concern having returned to the levels observed in the early 1970s, following a peak in the early 1990s. No distinctive patterns for the different types of environmental risk can be observed, which suggests that respondents fail to make a distinction between the different types. Finally, the data reveals that previous differences of opinion that correlated with levels of education and age have gradually been disappearing. The observed trends in environmental concern are best explained by macro factors, in particular the challenge-response model, the agenda-setting model, and the issue-entrepreneurship model.
Keywords: Environment; natural environment; Okolje; Risk; Tveganje; Public opinion; Javno mnenje; Mass media; Množični mediji; Slovenia; Slovenija